2020
DOI: 10.1016/j.chemosphere.2019.125457
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of the rare earth element neodymium in Mytilus galloprovincialis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The increased mobilisation and concentration of REEs in water systems could have significant impacts primarily to aquatic organisms (Freitas et al, 2020). The REE-content in seawater can be determined by factors relating to different input sources (e.g., terrestrial, hydrothermal) and scavenging processes related to depth, salinity, and oxygen levels (Greaves et al, 1999;Nozaki, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The increased mobilisation and concentration of REEs in water systems could have significant impacts primarily to aquatic organisms (Freitas et al, 2020). The REE-content in seawater can be determined by factors relating to different input sources (e.g., terrestrial, hydrothermal) and scavenging processes related to depth, salinity, and oxygen levels (Greaves et al, 1999;Nozaki, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As shown for Nd, Y, Ce, and La, the contents of individual REEs in the biomass of the macroinvertebrates were in the range of 10–70 nmol/g dry mass. These REE contents are generally an order of magnitude greater than values reported in the limited studies of pristine and human-impacted streams. , In addition, the Nd contents were about 5-fold higher than found in the tissue of a marine mussel experimentally exposed to 40 μg/L of Nd for a 4-week period . Further, the REE contents were intermediate between the contents for Pb and Cd, both of which are recognized trace metal toxicants for aquatic biota .…”
Section: Resultsmentioning
confidence: 64%
“…Published literature concerning REEs showed that aquatic organisms are able to uptake REEs from waters (Cyris, 2013;Rogowska et al, 2018;Freitas et al, 2020aFreitas et al, , 2020bMestre et al, 2019;Pinto et al, 2019) and from sediments (Pastorino et al, 2020). Like other chemical elements, Gd toxicity is influenced by the characteristics of the organisms exposed such as age, size, the type of exposure (chronicfor a long period of time; or acutefor a short period of time) and the concentrations of other REEs in solution.…”
Section: Gadolinium Bioaccumulation In Aquatic Organismsmentioning
confidence: 99%
“…Gadolinium and in general all REEs toxicity studies have focused particularly on species of economic interest or those related directly to public health, such as the bacteria Vibrio fischeri (González et al, 2015), the algae Raphidocelis subcapitata and those belonging to Chlorella species (Hao et al, 1997;Fujiwara et al, 2008;Balusamy et al, 2015;González et al, 2015;Joonas et al, 2017). Nevertheless, researches involving more marine and freshwater species have been reported recently, thus covering a greater biodiversity (Blaise et al, 2018;Pinto et al, 2019;Duarte and Caçador, 2020;Freitas et al, 2020aFreitas et al, , 2020bHenriques et al, 2019;Moreira et al, 2020).…”
Section: Gadolinium Bioaccumulation In Aquatic Organismsmentioning
confidence: 99%
See 1 more Smart Citation